Novel mulberry silkworm cocoon-derived carbon dots and their anti-inflammatory properties - Wang, Xiaoke; Zhang, Yue; Kong, Hui; Cheng, Jinjun; Zhang, Meiling; Sun, Ziwei; Wang, Suna; Liu, Jiaxing; Qu, Huihua; Zhao, Yan (Artificial cells, nanomedicine, and biotechnology, 2020)
Mulberry silkworm cocoon (MSC) carbonisata has been used for the treatment of inflammatory diseases for hundreds of years; however, after years of research efforts, little information is available on its anti-inflammatory components and underlying mechanism. We developed novel carbon dots (CDs) derived from MSC carbonisata (MSC-CDs), for the first time, with an average diameter of 2.26-9.35 nm and a quantum yield (QY) of 6.32%. The MSC-CDs were prepared using a modified pyrolysis method, and no further modification and external surface passivation agent was required. With abundant surface groups, MSC-CDs showed distinct solubility and bioactivity. In this study, we innovatively used three classical experimental models of inflammation to evaluate the anti-inflammatory bioactivity of MSC-CDs. The results indicated that MSC-CDs exhibited marked anti-inflammatory bioactivity which was likely mediated by inhibition of the expression of interleukin-6 and tumour necrosis factor-α. These results suggest that MSC-CDs possess a remarkable anti-inflammatory property, which provides evidence to support further investigation of the considerable potential and effective material basis of this traditional Chinese medicine.